2019
DOI: 10.1111/apha.13395
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CD36 protects against diet‐induced obesity but results in impaired muscle stem cell function, delayed muscle regeneration and hepatic steatosis

Abstract: Aim The prevalence of obesity is a major risk factor for cardiovascular and metabolic diseases including impaired skeletal muscle regeneration. Since skeletal muscle regenerative capacity is regulated by satellite cells, we aimed to investigate whether a high‐fat diet impairs satellite cell function and whether this is linked to fatty acid uptake via CD36. We also aimed to determine whether loss of CD36 impacts on muscle redox homeostasis and skeletal muscle regenerative capacity. Methods We studied the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 92 publications
(186 reference statements)
0
21
0
Order By: Relevance
“…Although it has been shown that there exists a negative correlation between obesity and the outcome after combined trauma injury, the molecular mechanisms remain unclear. Besides adverse effects and complication in the lung, obesity has also been shown to influence the regeneration of skeletal muscle ( Brown and Kuk, 2015 ; D’Souza et al, 2015 ; Li et al, 2020 ; Verpoorten et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that there exists a negative correlation between obesity and the outcome after combined trauma injury, the molecular mechanisms remain unclear. Besides adverse effects and complication in the lung, obesity has also been shown to influence the regeneration of skeletal muscle ( Brown and Kuk, 2015 ; D’Souza et al, 2015 ; Li et al, 2020 ; Verpoorten et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of articles addressing basic mechanisms related to obesity have recently appeared in Acta physiologica. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] One area of clinical relevance for obese patients is the immune system. Duan et al 20 recapitulate the connections between a high-fat diet and diseases.…”
mentioning
confidence: 99%
“…18 In addition, CD36, a mediator for fatty acid uptake in skeletal muscle, was identified as a link between obesity and skeletal muscle redox homeostasis and muscle regeneration. 19 When Verpoorten et al fed mice with a high-fat diet, the CD36 deficient group occurred to be protected from weight-gain in comparison to the wild-type mice. But perturbed satellite cell function in this group also did provoke negative effects on muscle homeostasis and regeneration.…”
mentioning
confidence: 99%
See 2 more Smart Citations